Swimming and cycling overloaded training in triathlon has no effect on running kinematics and economy - Palazetti, S.; Margaritis, I.; Guezennec, C. Y. (International Journal of Sports Medicine, 2005)
The aim of the study was to verify whether an overloaded training (OT) in triathlon deteriorates running kinematics (RK) and running economy (RE). Thirteen well-trained male long-distance triathletes (age: 28.1 ± 4.3 yrs; V·O2max: 65.0 ± 3.1 ml O2 · min-1 · kg-1) were divided into two groups: completed an individualized OT program (OG; n = 7) or maintained a normal level of training (NT) (CG; n = 6) for a duration of 3 weeks. Every week, each triathlete completed a standardized questionnaire to quantify the influence of training loads on mood state. To reach OT, total training load (h · 3 wk-1) was increased by 24 %; swimming and cycling total volumes were increased by 46 and 57 %, respectively, but the distance run was not modified in order to limit the risk of injuries. RK and RE were determined on treadmill test at 12 km · h-1 before and after the 3 weeks. The 3-week swimming and cycling OT in triathlon was sufficiently stressful to alter mood state but not to deteriorate the running kinematics and economy parameters in our previously well-trained male long-distance triathletes.